BASELINE DATA ON ANTHROPOGENIC PRACTICES IN THE AGRO-ECOSYSTEM OF POTHWAR PLATEAU, PAKISTAN - M. Sarwar; I. Hussain; M. Anwar; S. N. Mirza (Journal of Animal and Plant Sciences, 2016)
Human mediated changes have a marked impact on landscape structure as well as biodiversity in agricultural landscapes where continuous farming operations lead to the development of large-scale homogeneous farmland with reduced biodiversity. This study was conducted to collect baseline data about the activities of local people in the agro-ecosystem of Pothwar plateau, Pakistan through a questionnaire survey. Information reported by the selected 94 farmers revealed that wheat intercropped with mustard is a major crop cultivated in this region followed by groundnut and maize. Livestock grazing is common with goat most popularly reared. Cutting, harvesting (for fuel wood/animal feed) and burning of field boundary vegetation is not a common practice in Pothwar plateau. Agro-chemicals are used by 72% farmers to enhance crop yield. Except rodent pests of groundnut, the prevalence of pests and diseases was low in the study area. Consequently, few farmers employed chemical methods of pest control. Manual weeding is popular in the region. Environment education and awareness of local people about biodiversity and wildlife conservation is low and hunting is a common practice. This study generated useful baseline information that could be employed with other research studies for developing biodiversity conservation strategy in this agro-ecosystem.
Keywords: Agro-ecosystem; Anthropogenic practices; Human activities; Croplands